1998
DOI: 10.1007/s005350050157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of peripheral blood mononuclear cell stimulated with pyruvate dehydrogenase complex, T-cell receptors from patients with primary biliary cirrhosis

Abstract: Progressive destruction of the intrahepatic bile ducts in patients with primary biliary cirrhosis (PBC) is thought to be mediated by cytotoxic T cells which recognize certain epitopes, such as the pyruvate dehydrogenase complex (PDC). To clarify the T-cell repertoire in PBC, we analyzed T-cell receptor (TCR) Vbeta-chain messages expressed in peripheral blood mononuclear cells (PBMCs) stimulated with PDC and in liver biopsy specimens. PBMCs from 12 PBC patients and 6 healthy controls were examined. The TCR Vbet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Further, preferential usage of BV12 and conserved residues in the CDR3 region in liver‐infiltrating T cells of one out of two PBC patients has been described (16). More recently, Ochiai et al (20) provided evidence for clonal expansion of T cells in PBMC and liver biopsies by single strand conformation polymorphism (SSCP) analysis of the Vβ repertoire. The authors state that although no marked tendency towards T cell clonality in specific Vβ families was seen, clonal expansions were frequently observed for BV6, BV7 and BV13.2 (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, preferential usage of BV12 and conserved residues in the CDR3 region in liver‐infiltrating T cells of one out of two PBC patients has been described (16). More recently, Ochiai et al (20) provided evidence for clonal expansion of T cells in PBMC and liver biopsies by single strand conformation polymorphism (SSCP) analysis of the Vβ repertoire. The authors state that although no marked tendency towards T cell clonality in specific Vβ families was seen, clonal expansions were frequently observed for BV6, BV7 and BV13.2 (20).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ochiai et al (20) provided evidence for clonal expansion of T cells in PBMC and liver biopsies by single strand conformation polymorphism (SSCP) analysis of the Vβ repertoire. The authors state that although no marked tendency towards T cell clonality in specific Vβ families was seen, clonal expansions were frequently observed for BV6, BV7 and BV13.2 (20). In addition, some of the T cell clonotypes showed the same mobility in SSCP gels in both unstimulated PBMC, and PBMC stimulated with PDC, suggesting an accumulation of common clonal T cells specific for the autoantigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that T cells infiltrating the liver in PBC consisted of multiple clonotypes and that restricted T-cell clones accumulated in the liver were also present in peripheral blood lymphocytes. However, as Ochiai et al 1 point out in this issue of the Journal, there have been no reports on the analysis of TCR in T cells which have been stimulated with a plausible real autoantigen.…”
mentioning
confidence: 99%
“…Thus, T-cell responses can be altered by molecular mimicry or by amino acid substitutions of MHC molecules or antigenic peptides, i.e., TCR ligands, and such peptide analogues can induce qualitative changes in T cells; T cell anergy, T cell antagonism, or changes in proliferative responses and lymphokine production 6,7 Consequently, the application of such altered peptides, in which pathogenic T cells can be selectively regulated without adverse effects such as systemic immunosupression, is considered to be a possibly promising approach to the treatment of autoimmune diseases. 17 The study by Ochiai et al 1 indicates the direction in which further studies on PBC should proceed. Clarification of these questions may provide new insights into the pathogenesis of PBC.…”
mentioning
confidence: 99%